(untitled) (Scientific journal of the Fergana State University, 2026)
This article analyzes the shared history, cultural ties, and modern strategic partnership of the peoples of Uzbekistan and Azerbaijan under the slogan “One History, One Destiny.” The materials are based on Heydar Aliyev’s ideas about the synthesis of Azerbaijani culture and substantiate that the two nations are bound by the ties of blood, language, and spirit. The study focuses on the educational and enlightenment movements of the early 20th century, examining the activities and tragic fate of the prominent Turkologist Bakir Choponzoda (1893–1937) as an example of the common repressive trials faced by the intellectuals of both nations. In particular, the article analyzes his scholarly legacy at Fergana State University (1930–1935) and his role in establishing the Department of Uzbek Language and Literature. It highlights that, thanks to the political will of President Shavkat Mirziyoyev and President Ilham Aliyev, the relations between the two countries have reached the level of strategic partnership. The strengthening of economic ties (the Baku–Tbilisi–Kars railway) and cultural cooperation (the Heydar Aliyev Center in Tashkent and the Alisher Navoi monument in Baku) is emphasized. The article concludes that studying the heritage of Jadid scholars like Bakir Choponzoda plays an important role in consolidating unity and cooperation within the Organization of Turkic States and promoting the ideals of a new Renaissance.